Respuesta :

So all you really need to do is to substitute the value of x into the equation so like the 1st one will look like this:[tex]f(-3) = 2(-3) + 4 = -2 \\ f(-1) = 2(-1) + 4 = 2 \\ f(0) = 2(0) + 4 = 4 \\ f(2) = 2(2) + 4 = 8 \\ f(4) = 2(4) + 4 = 12[/tex]Those would be the right column for the f(x) values
Now do the same for g(x)[tex]g(-3) = (-3)^2+1 = 10 \\ g(-1) = (-1)^2 + 1 = 2 \\ g(0) = 0^2 + 1 = 1 \\ g(2) = 2^2 + 1 = 5 \\ g(4) = 4^2 + 1 = 17[/tex]
You will notice that when x = -1, g(x) = f(x)